PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN MEDIA TIKTOK TERHADAP KEMAMPUAN MENULIS TEKS BERITA SISWA KELAS VII MTsN 2 SIMALUNGUN - Maraendar, Akbar; J. Daulay, Muhammad Anggie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to (1) To analyze the skills of writing news texts using the Think Pair Share (TPS) learning model assisted by TikTok social media in class VII students of MTs Negeri 2 Simalungun. (2) To analyze the skills of writing news texts using the Contextual Teaching and Learning (CTL) learning model assisted by TikTok social media in class VII students of MTs Negeri 2 Simalungun. (3) To analyze the effect of the Contextual Teaching and Learning (CTL) learning model assisted by TikTok social media on the skills of writing news texts in class VII students of MTs Negeri 2 Simalungun. In this study, the research method used is an experimental method with the research design used in this study, namely Two Group Post Test Design. This study involved all class VII students of MTs 2 Simalungun, totaling 196 people with a sample of 64 people divided into two classes, namely class VII4 as a control class with a total of 32 students and class VII-3 as an experimental class with a total of 32 students. The instruments used in the study included the appropriateness of the news headline, news text structure, news text elements, sentence/spelling and punctuation accuracy, word choice, use of standard words, use of direct sentences, temporal conjunctions, adverbs, and subordinate verbs. Data analysis techniques used in the study included requirements analysis tests, normality tests, homogeneity tests, and hypothesis tests. The results showed that news text writing skills using the Contextual Teaching and Learning (CTL) learning model assisted by TikTok social media had a significant impact, as evidenced by the calculated t value (5,771) > t table (1.697), indicating a significant influence on the news text writing skills of seventh-grade students at MTsN 2 Simalungun.